CD20+ tumor‐infiltrating immune cells and CD204+ M2 macrophages are associated with prognosis in thymic carcinoma. Issue 6 (8th May 2020) - Sato, Jun; Kitano, Shigehisa; Motoi, Noriko; Ino, Yoshinori; Yamamoto, Noboru; Watanabe, Shunichi; Ohe, Yuichiro; Hiraoka, Nobuyoshi
Abstract: Thymic carcinoma is a rare malignant disease with no standard systemic chemotherapy. The purpose of the present study was to investigate tumor‐infiltrating immune cells (TIIC) in the tumor microenvironment (TME), focusing on the impact of TIIC and program death‐ligand 1 (PD‐L1) expression on clinical outcomes in thymic cancer. Patients with thymic carcinoma resected between 1973 and 2017 were investigated. The tissue specimens were analyzed through immunohistochemical staining to elucidate the prognostic effects of TIIC, their ratios and PD‐L1 in a preliminary cohort (n = 10). The density of TIIC as well as PD‐L1 expression was evaluated in intraepithelial and tumor‐stromal areas on the representative whole section of tumors. The immune factors showing significant association with disease‐free survival (DFS) were evaluated in the total cohort (n = 42). TIIC in the preliminary population showed no significant difference between the two groups. However, CD8, CD20, CD204, FOXP3 and CD20/CD204 ratio demonstrated a tendency to act as predictive markers for recurrence. In the total cohort, significant differences were observed for CD8 +, CD20 + and CD204 + cells in tumor islets, and for CD8 +, CD20 + and FOXP3 + cells as well as the CD8/CD204 and CD20/CD204 ratios in the stroma, indicating their prognostic effect. The prognostic effect of the PD‐L1 expression in tumor cells could not be established, possibly because of intratumoral heterogeneity. CD8, CD20 and CD204 positive TIIC in stroma were identified as possible better prognostic biomarkers, considering the heterogeneity of other biomarkers. The present study paves the way for exploring strategies of combination immunotherapy targeting B cell immunity in thymic carcinoma. Abstract : The present study revealed that CD8 +, CD20 + and CD204 + tumor‐infiltrating immune cells in cancer stroma might be prognostic biomarkers, considering the heterogeneity of other biomarkers, including PD‐L1 expression on tumor cells in thymic carcinoma.